2022
DOI: 10.1007/s10103-022-03656-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of lasers and aPDT in elimination of intraoral halitosis: a systematic review based on clinical trials

Abstract: In recent years, there has been increasing interest in research showing positive results in antimicrobial photodynamic therapy (aPDT) and laser therapy (LT) in dentistry. The authors of this review tried to answer the question: “Is the effectiveness of lasers and aPDT in the elimination of intraoral halitosis possible?” For this purpose, the electronic database of PubMed and Cochrane Library were searched until September 2021 using a combination of different keywords: (bad breath OR fetor ex ore OR halitosis O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…All studies incorporated into the systematic review were required to adhere to the following criteria: they had to investigate discrepancies in cephalometric analysis results between orthodontists and radiologists, as well as between orthodontists and artificial intelligence (AI), encompassing both manual and digital methods of analysis. Additionally, studies needed to be published in English, with no restrictions on the publication date [26,[28][29][30][31][32][33][34][35][36][37][38]. The authors of this review established the following exclusion criteria: studies written in languages other than English, comparisons solely between two orthodontists, clinical reports, opinions, editorial papers, review articles, and studies lacking a full-text version [26,[28][29][30][31][32][33][34][35][36][37][38].…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…All studies incorporated into the systematic review were required to adhere to the following criteria: they had to investigate discrepancies in cephalometric analysis results between orthodontists and radiologists, as well as between orthodontists and artificial intelligence (AI), encompassing both manual and digital methods of analysis. Additionally, studies needed to be published in English, with no restrictions on the publication date [26,[28][29][30][31][32][33][34][35][36][37][38]. The authors of this review established the following exclusion criteria: studies written in languages other than English, comparisons solely between two orthodontists, clinical reports, opinions, editorial papers, review articles, and studies lacking a full-text version [26,[28][29][30][31][32][33][34][35][36][37][38].…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Additionally, studies needed to be published in English, with no restrictions on the publication date [26,[28][29][30][31][32][33][34][35][36][37][38]. The authors of this review established the following exclusion criteria: studies written in languages other than English, comparisons solely between two orthodontists, clinical reports, opinions, editorial papers, review articles, and studies lacking a full-text version [26,[28][29][30][31][32][33][34][35][36][37][38].…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…examined the effectiveness of lasers and aPDT in eliminating intraoral halitosis from 1994 to September 2021. 108 They found that in most studies on aPDT, MB and 660 nm laser were employed. Almost all the studies in the review indicated that aPDT was an effective treatment for bad breath.…”
Section: Applications In Oral Infectionmentioning
confidence: 99%
“…This method has numerous advantages, such as the minimization of tissue injury and the prevention of bacterial resistance development [ 54 , 56 ]. According to recent systematic reviews, antimicrobial photodynamic therapy has the ability to efficiently eliminate bacteria responsible for the production of VSC, and it is an effective approach for managing halitosis for a longer duration compared to conventional treatments such as tongue scrapers for this condition [ 54 , 57 ].…”
Section: Reviewmentioning
confidence: 99%